A life dedicated to surgery: Serhii Tymofieiev’s contribution to medicine and education - Tsiura, Y. P.; Kryvopustov, M. S. (General Surgery, 2024)
Serhii Lukianovych Tymofieiev (1875—1943) was a renowned physician, surgeon, scientist, and teacher in the history of Ukrainian medicine. Continuous education and practice shaped his professional career, which began in the Kherson province. Tymofieiev became a Doctor of Medical Sciences after defending his dissertation on the pathogenesis of renal edema. His contribution covers several medical fields, including orthopedics, traumatology, urology, and military surgery. Serhii Lukianovych founded the Department of Traumatology and Orthopedics at the Kyiv Medical Institute, which became the basis for the development of modern Ukrainian orthopedics. He developed innovative approaches to the treatment of injuries, reconstructive surgery, and the training of future doctors. During World War I, Tymofieiev headed the surgical department of the Kyiv Military Hospital, where he treated gunshot wounds. His pedagogical activity was focused on improving the teaching of military field surgery, a topic that is particularly relevant during times of military conflicts. Tymofieiev not only worked tirelessly but also educated a generation of doctors who continued his legacy. Having written more than 90 scientific works, he became one of the founders of Ukrainian surgery and medical education. His life path is an example of high professionalism, extensive scientific knowledge, and commitment to the medical profession. Tymofieiev made a significant contribution to the history of medicine, and his legacy continues to inspire modern doctors.